Dance in Ancient Egypt - Spencer, Patricia (Near Eastern archaeology, 2003)
Devotees of ancient Egyptian art are familiar with numerous tomb paintings depicting dancers in various forms of dress and many different postures. Tracing depictions of Egyptian dancers from Pre-Dynastic to Hellenistic times, the author presents a survey of the history and uses of dance in ancient Egypt. Using both textual and pictorial material, she delves into the commemorative, religious and entertainment value of dance in ancient Egyptian life.